Replication Dynamics for Six Gram-Negative Bacterial Species during Bloodstream Infection - Mark T. Anderson (American Society for Microbiology, 2021)
ABSTRACT Bloodstream infections (BSI) are a major public health burden due to high mortality rates and the cost of treatment. The impact of BSI is further compounded by a rise in antibiotic resistance among Gram-negative species associated with these infections. Escherichia coli, Serratia marcescens, Klebsiella pneumoniae, Enterobacter hormaechei, Citrobacter freundii, and Acinetobacter baumannii are all common causes of BSI, which can be recapitulated in a murine model. The objective of this study was to characterize infection kinetics and bacterial replication rates during bacteremia for these six pathogens to gain a better understanding of bacterial physiology during infection. Temporal observations of bacterial burdens of the tested species demonstrated varied abilities to establish colonization in the spleen, liver, or kidney. K. pneumoniae and S. marcescens expanded rapidly in the liver and kidney, respectively. Other organisms, such as C. freundii and E. hormaechei, were steadily cleared from all three target organs throughout the infection. In situ replication rates measured by whole-genome sequencing of bacterial DNA recovered from murine spleens demonstrated that each species was capable of sustained replication at 24 h postinfection, and several species demonstrated <60-min generation times. The relatively short generation times observed in the spleen were in contrast to an overall decrease in bacterial burden for some species, suggesting that the rate of immune-mediated clearance exceeded replication. Furthermore, bacterial generation times measured in the murine spleen approximated those measured during growth in human serum cultures. Together, these findings provide insight into the infection kinetics of six medically important species during bacteremia. IMPORTANCE Bloodstream infections are a global public health problem. The goal of this work was to determine the replication characteristics of Gram-negative bacterial species in the host following bloodstream infection. The number of bacteria in major organs is likely determined by a balance between replication rates and the ability of the host to clear bacteria. We selected a cohort of six species from three families that represent common causative agents of bloodstream infections in humans and determined their replication rates in a murine bacteremia model. We found that the bacteria grow rapidly in the spleen, demonstrating that they can obtain the necessary nutrients for growth in this environment. However, the overall number of bacteria decreased in most cases, suggesting that killing of bacteria outpaces their growth. Through a better understanding of how bacteria replicate during bloodstream infections, we aim to gain insight into future means of combating these infections.